The role of endoplasmic reticulum stress in BPS-induced disruption of endometrial decidualization - Shaoyuan Xu; Zhaoping Tan; Ruiqing Zhang; Jiawei Kang; Zhenzhen Zhang; Qin Fu; Yun Tao; Yao Xiong; Yuanzhen Zhang (Ecotoxicology and Environmental Safety)
Bisphenol A (BPA) exposure has been widely associated with adverse health outcomes, prompting the proliferation of ''BPA-free'' products. However, substitutes such as bisphenol S (BPS) are now equally prevalent and frequently detected at levels comparable to BPA. Our previous research identified BPA as an endocrine disruptor impairing reproductive systems. This study investigates the underexplored effects of BPS on endometrial decidualization and its underlying mechanisms. Serum and urine samples from infertility patients undergoing assisted reproductive technologies (ART) were analyzed for BPS concentrations, revealing a significantly lower implantation rate in the high serum BPS group compared to the low BPS group (37.5 % vs. 58.1 %, P = 0.048). Urinary BPS levels were elevated in patients with recurrent implantation failure (RIF) relative to controls (0.24 vs. 0.15 ng/mL). In vitro, human endometrial stromal cells (HESCs) exposed to BPS (100 pM–1 µM) during hormonally induced decidualization exhibited suppressed proliferation and reduced decidualization markers (PRL and IGFBP1). BPS exposure triggered endoplasmic reticulum (ER) stress, evidenced by elevated levels of ER stress-related proteins (XBP1-s, ATF4, and IRE1α), ultrastructural ER abnormalities observed via transmission electron microscopy, and increased immunostaining of IRE1α and ATF4 in RIF endometrial tissues. ER stress inhibitors (TUDCA and MKC8866) mitigated these effects and restored decidualization markers. Our findings suggest that BPS contamination may contribute to implantation failure by disrupting HESC decidualization through ER stress activation.